1756-1776 N.C. Sess. Laws 168 - (:unkn) unknown (My University, 1768)
An Act To Amend An Act Entitled, "An Additional Act To An Act, Entitled, An Act To Prevent Killing Deer At Unseasonable Times, And For Putting A Stop To Many Abuses Committed By White Persons Under Pretense Of Hunting, ch. 13: Whereas by the before recited act, persons who have no settled habitation, or not tending five thousand corn hills, are prohibited from hunting, under the penalty of five pounds, and forfeiture of his gun[.]
Keywords: HUNTING REGULATION